A Comparative Study On Consumers' Attitudes Towards Genetically Modified Food Between Malaysia and UK - Chin, Wu Leong Jovan (2016)
Many previous studies on consumers’ attitudes towards genetically modified (GM) food were done on developed countries. Despite limited studies being done on developing countries, it has been revealed that consumers in developing countries have positive attitudes towards GM food, which differs from consumers in developed countries. As such, the purpose of this comparative study is to explore the differences in consumers’ attitudes towards genetically modified (GM) food in the United Kingdom (UK) (developed country) against Malaysia (developing country) and how the factors influencing their attitudes differ between the two countries. This study employs qualitative-based research methods with an in-depth semi-structured interview for data collection and template analysis for data analysis. The findings of this study have revealed that Malaysian participants have positive attitudes towards GM food whereas UK participants have ambivalent attitudes consisting of positive, negative and no-stand attitudes. Out of the three factors analyzed – benefits and risks perceptions, individual values and knowledge on GM food, benefits and risks perceptions were the main factor in influencing their attitudes. However, Malaysian participants viewed benefits and risks through a compensatory relationship whereas UK participants viewed risks as obstacles for acceptance of benefits of GM food. It has also been highlighted that objective knowledge on GM food is a prominent factor as compared to individual values in influencing the participants’ attitudes towards GM food. This study has also revealed that the three factors are interconnected in influencing the participants’ attitudes towards GM food. These findings have theoretical and managerial implications, which were suggested in this study.